No response to changes in marginal incentives in one-shot public good experiments - Natalie Struwe; Esther Blanco; James Walker (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
We report novel results from changes in the marginal per capita return (MPCR) in a one-shot public good game where participants make a single provision decision. Data was collected using three "data collection processes": an online experiment conducted on Prolific, an online experiment conducted with a subject pool of university students, and an experiment implemented following the conventional procedures of the economic laboratory with university students. In three between-subject treatment conditions, we confront participants from each of these three samples with either a low MPCR of 0.4, a high MPCR of 0.8 holding constant the individual endowment, or a high MPCR of 0.8 reducing the individual endowment to hold constant maximum possible group earnings. Based on a total sample size of 952 participants, we find that, unlike results from previous experiments where subjects make multiple contribution decisions in varying experimental designs, contributions to the public good are not different for the different MPCR conditions we study. We consider these results to be highly relevant in highlighting the limits to our understanding of cooperative behavior for settings without repeated interactions.
Keywords: C91; C92; H41; 330; Voluntary contribution mechanism; Public goods; Marginal per capita return; Social dilemma; Experiments